HABITUASI SISWA DALAM EKSTRAKURIKULER MARCHING BAND DI SMAN 1 CIOMAS - Romdhoni, Mochamad; Irfani Lindawati, Yustika; Soetrisnaadisendjaja, Denny (Saskara : Indonesian Journal of Society Studies, 2021)
Education plays an active role in shaping the habituation of students to have good character and behaviour at school. This study is aimed to find out and describe a process of habituation of character values and the role of extracurricular of Marching Band in building characters of the students at SMAN 1 Ciomas. This research method used a qualitative through the descriptive approach. Data collection techniques used were observation, interview and documentation techniques. The subjects of this study consisted of members and extracurricular trainers of the Marching Band, counselling teachers and homeroom teachers. The results of the study showed the existence of habituation in extracurricular of Marching Band at SMAN 1 Ciomas which was able to play role in building the character values of students in each process through four aspects of cultural reproduction, which are habitus, capital (capital), arena (realm) and symbolic violence. The character values of Marching Band extracurricular students (members) are realized in the behaviour and disciplinary action of time, dressed in uniform, responsibility, consistency, enthusiasm, focus, respect for the coach, honest and having a soul leader.